The wind from the east : French intellectuals, the cultural revolution, and the legacy of the 1960s - Wolin, Richard (Princeton University Press : Princeton University Press, 2018)
Combining a merciless exposé of left-wing political folly and cross-cultural misunderstanding with a spirited defense of the 1960s, this book tells the colourful story of this legendary period in France.